A bibliometric analysis of gene editing and amyotrophic lateral sclerosis (from 2004 to 2024) - Wan, Hejia; Qian, Wenli; Wei, Bingqi; Tian, Kaiyue; Chen, Ziyi; Zhang, Jiong; Chen, Fang (Frontiers in Neuroscience, 2024)
ObjectiveTo learn more about gene editing and ALS, and to provide a comprehensive view of gene editing for further treatment of amyotrophic lateral sclerosis.MethodsWe searched 1981 records from Web of Science core collection and Pubmed, Scopus, of which 1,292 records were obtained after exclusion. We then scientifically and metrologically analyzed these records for spatial and temporal distribution, author distribution, subject categories, subject distribution, references, and keywords using R, software CiteSpace and VOSviewer.ResultsOur analysis provides basic information about research in the field, suggests that the field has stabilized over the past decade, and identifies potential partners for interested researchers. Current research in this area is focused on inflammatory mechanisms, immune mechanisms, related diseases, and associated cytokines in ALS.ConclusionRNA Editing, Antisense Bligonucleotide, and Glycine Receptor are cutting-edge research topics in this field, which is undergoing rapid development. We hope that this work will provide new ideas for advancing the scientific research and clinical application of ALS.